High Performance NiOx Extended-Gate Field-Effect Transistor Biosensor for Detection of Uric Acid. Issue 1 (27th January 2021) - Pan, Tung-Ming; Lin, Chen-Hung
Abstract : In this paper, we developed a high performance NiOx extended-gate field-effect transistor (EGFET) biosensor for detection of uric acid. The structural and sensing properties of the NiOx sensing film deposited on a n + -type Si substrate was examined for an EGFET pH sensor. X-ray diffraction, atomic force microscope and X-ray photoelectron spectroscopy were used to analyze the film features of the NiOx sensing film. The NiOx sensing film based on EGFET exhibited a high pH sensitivity of 58.53 mV pH −1, a small hysteresis voltage of 1.4 mV and a low drift rate of 0.30 mV h −1 . Moreover, the NiOx EGFET biosensor showed a high linearity in the uric acid range between 1 and 30 mg dl −1 . In addition, this NiOx EGFET biosensor demonstrated a very good selectivity to uric acid over other interfering substrates (ascorbic acid, glucose, urea).